Deployment Of Gross Profit Loss For Attenuating Time Loss Impact In Automotive Industries - Abdul Rasib, Amir Hamzah; Ebrahim, Zuhriah; Muhamad, Mohd Razali (International Journal of Scientific and Technology Research, 2019)
Time Loss (TL) occurs along the production processes that have a significant effect on productivity and able to influence the monetary loss in the manufacturing industry. TL becomes critical when an assembly process involves a high product variety in the same production line. The aim of this study is to provide a measure for Gross Profit Loss (GPL)based on Production Capacity Loss (PCL) result. Then, the equation for Production Capacity Loss (PCL) was derived based on the structure of Time Loss Measures (TLM) components known as: (i) Non-valued Changeover Time (NVCOT), (ii) Inefficient Processing Time (IPT), (iii) Unnecessary Overtime (UOT), and (iv) Non-conformance Time (NCT). The TLM had been developed through a thorough literature study on manufacturing operations. In economic view, PCL can be converted into Gross Profit Loss (GPL). Finally, the GPL equation were validated by using case study at five automotive manufacturing companies in Malaysia. The results of the case study show that GPL did occur through the four TLM components that caused an amount of PCL. In conclusion, GPL can be used as a measuring tool for the manufacturing companies to monitor continuously the operational performance of the manual assembly process and semi-auto assembly process in monetary unit.